Patterns and Drivers of Pine Processionary Moth Defoliation in Mediterranean Mountain Forests - Gazol, Antonio; Hernández-Alonso, Rodolfo; Camarero, J. Julio (Frontiers in Ecology and Evolution, 2019)
Insect defoliations are one of the threats of forests health, and climate warming may enhance the occurrence of more severe outbreaks. Thus, understanding the spatial and temporal patterns of insect defoliation may provide valuable information to infer their responses to climate change. To contribute to this question, we studied a 42-year long record of defoliation by pine processionary moth (Thaumetopoea pityocampa, hereafter PPM), a major defoliating insect of Mediterranean conifers. We tested the hypothesis that climate warming is increasing PPM defoliation, which occurs in winter, and enhancing its upward shift. We analysed data corresponding to PPM defoliation affecting 92 stands of four pine species distributed across an altitudinal (1030-1695 m) gradient (going downwards: Pinus sylvestris, Pinus nigra, Pinus pinaster and Pinus halepensis) located near Mora de Rubielos (Teruel, Spain). We found a higher prevalence of PPM defoliation in P. nigra stands followed by P. sylvestris. PPM defoliation showed several peaks (1979-1983, 1991-1992 and 1995-1996) and it was positively related to winter minimum temperatures, with temperatures below -12 ºC reducing PPM defoliation. We found higher defoliation in stands dominated by P. nigra, located at intermediate altitude and with low tree density. We did not detect any upward shift of PPM defoliations. PPM defoliation dynamics depend on forest structure and on forest composition, but it might also be impacted by the occurrence of lethal temperatures below a threshold. These patterns should be considered when forecasting the range expansion of forest insects in response to climate warming.